Pengaruh Kompensasi Finansial, Motivasi Kerja dan Kepemimpinan Terhadap Kepuasan kerja Karyawan di Kakiang Bungalow Ubud bali - Hanggara, I Made Dwi; Supartha, Wayan Gede (E-Jurnal Manajemen, 2014)
This research has a purpose to research that there is a significant influence simultaneously, partially  and dominantly between financial compensation, job motivation leadership variables to Kakiang Bungalow Ubud’s employee job satisfaction by taking 45 people as samples including all employees, not include the head of company. Data used are primary and secondary data. Analysis used are simultaneous test (f test) and partial test (t test) also couple linear regression to know the relation between variable x and variable y. Based on the analysis, that job motivation financial compensation variable and leadership simultaneously and partially has significant influences to employee job satisfaction and variable that has dominant influence is leadership variable. So management has to be more increasing incentive, future security and  delegates authority in the company. Keywords : job satisfaction, financial compensation, job motivation, leadership